Enhancing Listening Skills through Paired Storytelling Model with Wayang Cartoon Media in Indonesian Language Learning - Khafid Taftahjani; Kuntoro Kuntoro; Pujiani Pujiani (UM Purwokerto Press, 2023)
This research is motivated by the fact that Indonesian language learning, particularly in listening skills, faces various challenges for both students and teachers. Students lack interest and feel bored, while teachers struggle to cultivate students' motivation and have difficulties in implementing and selecting innovative and varied teaching models that align with the learning material. There are also challenges in developing teaching materials. Teaching still relies on conventional and classical methods through strategies, approaches, and teaching methods that have not fostered productive thinking habits. Teachers should be skilled in selecting teaching media to ensure effective and enjoyable teaching and learning processes and enhance students' competence in listening to fairy tales. By utilizing the paired story telling learning model through the